Dietary characteristics of women with gestational diabetes mellitus - Hasbullah, Farah Yasmin; Yong, Heng Yaw; Mohd Shariff, Zalilah; Rejali, Zulida; Adam, Noor Lita; Mohd Yusof, Barakatun Nisak (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: The role of dietary intake on maternal glucose is uncertain. This study described the dietary characteristics of women with gestational diabetes mellitus (GDM) and examined the differences in dietary characteristics based on GDM diagnosis. Methods: This study recruited GDM women (n =45; age =31.1±5.1 years old) from health clinics in Seremban. Dietary intake, glycemic index (GI) and glycemic load (GL) were assessed using a semi-quantitative food frequency questionnaire (SFFQ) during first and second trimester of pregnancy. GDM diagnosis was made at 28 weeks gestation with the following cut-off for FPG ≥ 5.1 or 2hPG ≥ 7.8 mmol/L following oral glucose tolerance test. Results: Women with GDM had a reasonable intake of protein and fat but consumed high-carbohydrate at second trimester and high-sugar diet at both trimesters. Fibre, iron and calcium from the food sources did not meet the recommended nutrient intakes for pregnancy. About 75.6% (n = 34) GDM women had high 2hPG (9.3 ± 1.5 mmol/L) with a normal FPG (4.7 ± 0.7 mmol/L). While dietary characteristics were not significantly different, women with a higher 2hPG tended to take a higher proportion of protein at first trimester and a higher dietary GI, serving of rice, and sugars and creamer at second trimester than high FPG. Conclusion: Suboptimal maternal nutrition in women with GDM are of particular concern. Dietary characteristics of women with high fasting and 2-hour glucose were comparable but not optimal. The needs of tailored nutritional intervention are evident in women known to be at high risk of GDM.